INITIATING STRUCTURE DAN CONSIDERATION DALAM KEPEMIMPINAN KEPALA SEKOLAH: ANALISIS MIXED METHOD BERBASIS SIMULASI ROLEPLAY TERHADAP KINERJA GURU DI SMK KETINTANG SURABAYA - Oryza Syafira; Aulia Ramadhani; Tiana Albania Imama; Evania Sari; Shafira Rahmadini; Erny Roesminingsih (STKIP Pesisir Selatan, 2026)
This study aims to analyze the implementation of principal leadership based on the Ohio State Theory and its relationship to teacher performance at SMK Ketintang Surabaya. The study used a mixed methods approach with a sequential explanatory design. Qualitative data were obtained through interviews with the vice principal, teachers, and students, while quantitative data were obtained through student assessments as peer assessors of roleplay simulations based on field findings. The results of the study indicate that: (1) the principal applies the dimensions of initiating structure and consideration in a balanced manner through target setting, task division, supervision, open communication, and professional support to teachers; (2) the research instrument was declared valid and reliable; and (3) the relationship between Ohio State leadership and teacher performance was classified as very weak with a correlation coefficient of 0.062, a significance of 0.743 (>0.05), and a determination coefficient of 0.4%. The novelty of this study lies in the use of an integrative approach that combines field interviews and roleplay simulations to examine principal leadership in the context of the implementation of the Independent Curriculum at SMK.